PENGARUH UPAH DAN BAHAN BAKU TERHADAP PRODUKTIVITAS TENAGA KERJA DAN PRODUKSI FURNITURE KAYU KABUPATEN GIANYAR - Ratikatama, Ngakan Made Rama; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The development of industry in Indonesia is highly expected by the government to improve the national economy but does not rule out other sectors. The furniture industry is a sector that has very high prospects because it is supported by the vast forests owned by Indonesia. The handicraft industry is growing rapidly in Bali as a support for the tourism sector, one of which is in Gianyar Regency. The purpose of this study was to analyze the effect of wages and raw materials on labor productivity and wood furniture production in gianyar district. This research is sourced from primary data from 40 industries in Gianyar. Data collection method is done through interviews with respondents. The analysis technique used is the path analysis technique. The results of data analysis showed that Wages results directly had a significant negative effect on the work productivity of the furniture industry in Gianyar Regency. Raw materials directly have a positive and significant effect on the productivity of the furniture industry in Gianyar Regency. Wages, raw materials and labor productivity have a positive and significant effect on the production of wood furniture in Gianyar Regency. Keywords: wages, raw materials, productivity, and production.